THU0573 Development of a Pediatric Rheumatology Education Resource-Sharing Website: If You Build it, Will they Come?. (9th June 2015) - Curran, M.; Singh, R.
Abstract : Background: Deficiencies in pediatric rheumatology teaching are well described in medical literature, necessitating innovative means for education. Currently, no websites exist to help training programs improve teaching. Objectives: The objectives of this project are 1) to create a user-friendly website providing support for educators by curating and sharing teaching materials and 2) to study site usage and effectiveness. An ongoing study aims to assist pediatric training programs in increasing the quality and quantity of rheumatology education. Methods: OuchMyLeg! (https://ouchmyleg.northwestern.edu ) was designed using Drupal with security measures to protect user confidentiality. Research personnel verify that accounts belong to medical educators before approval. Users belong to either the PRIME community for practicing physicians (mainly pediatric rheumatologists) interested in medical education or the chief resident (CR) community for supervisors of pediatric training programs. Users may link to publicly available educational resources, upload personal instructional materials such as slide sets, documents and videos and download materials posted by others. Copyright infringement rules are posted. PRIME community members were recruited through an email listserv and ads at two pediatric rheumatology conferences. Chief residents were invited by emails sent to all U.S. pediatric training program administrators. CR users were required to tick a box giving consent to be a study subject and take a needs assessment survey before accessing site materials. Usage statistics were collected with Google Analytics. Results: As of January 2015, the PRIME community has 204 users from 40 countries: USA-156, Canada-11, UK-6, Brazil-3, Germany-3, India-3, Israel-3, Hungary-2, Jordan-2, Saudi Arabia-2, Spain-2 and one each from Colombia, France, Italy, Mexico, Latvia, the Netherlands, Singapore, Slovenia, South Africa, Sweden and Turkey. Members include pediatric rheumatologists-164, fellows-27, nurses-8 and research associates-5. 205 training program administrators were emailed, 74 (36%) expressed interest by providing chief resident contact information, 136 chief residents were invited to join the CR community, 61 signed up for an account and 31 (23%) completed the entrance survey. 25 public (pub) resources are available to both communities. 5 users posted a total of 18 private (pri) resources. Resources include links to websites containing cases, review articles, interactive tutorials and clinical phone applications (13 pub), rheumatology curriculum materials (3 pub), image banks (2 pub), instructional videos (2 pub), musculoskeletal exam instruction (1 pub), education guidelines (1 pub), case studies (3 pub, 1 pri), exam study materials (1 pub, 3 pri), disease-based lectures (10 pri), a pediatric rheumatology primer (1 pri) and an instructional technique lecture (1 pri). Conclusions: The creation of a members-only instructional materials-sharing website was feasible. Recruitment for the PRIME community was successful with over 200 worldwide users. Recruitment for the CR community was less successful possibly due to the entry survey requirement. Only 2.5% of PRIME members posted resources indicating reluctance to share personal teaching materials. User feedback will address barriers to sharing. The CR community study is ongoing. We hope to prove website usability and educational improvement. Disclosure of Interest: None declared